Impact of Artificial Intelligence and Automation on Project Management Processes - Naji Mohammed Naji Nasr; Assedeq Assanousi Asharee (المجلة الأفروآسيوية للبحث العلمي, 2024)
This paper explores the impact of Artificial Intelligence (AI) and automation on project management processes, focusing on how AI-driven tools enhance efficiency, accuracy, and adaptability. It discusses AI’s role in planning, scheduling, execution, monitoring, and risk management, highlighting how predictive analytics, automated dashboards, and adaptive strategies contribute to improved project outcomes. The study adopts a mixed-method approach, utilizing both qualitative insights from interviews and case studies and quantitative data from surveys to analyze AI’s influence on project management. While AI offers significant benefits, it also presents challenges like resistance to change, skill gaps, ethical concerns, and data privacy issues. Recommendations include phased AI implementation, staff training, and strategic change management to ensure effective adoption. The findings suggest that AI has the potential to redefine traditional project management roles, emphasizing data-driven decision-making and proactive risk management.